Neural Processes Underlying Mirror-Induced Visual Illusion: An Activation Likelihood Estimation Meta-Analysis - Bello, Umar Muhammad; Kranz, Georg S.; Winser, Stanley John; Chan, Chetwyn C. H. (Frontiers in Human Neuroscience, 2020)
Introduction: Neuroimaging studies on neural processes associated with mirror-induced visual illusion (MVI) are growing in number. Previous systematic reviews on these studies used qualitative approaches. Objective: The present study conducted activation likelihood estimation (ALE) meta-analysis to locate the brain areas for unfolding the neural processes associated with the MVI. Method: We searched the CINAHL, MEDLINE, Scopus and PubMed databases and identified eight studies (with 14 experiments) that met the inclusion criteria. Results: Contrasting with a rest condition, strong convergence in the bilateral primary and premotor areas and the inferior parietal lobule suggested top-down motor planning and execution. In addition, convergence was identified in the ipsilateral precuneus, cerebellum, superior frontal gyrus and superior parietal lobule, clusters corresponding to the static hidden hand indicating self-processing operations, somatosensory processing, and motor control. When contrasting with an active movement condition, additional substantial convergence was revealed in visual-related areas, such as the ipsilateral cuneus, fusiform gyrus, middle occipital gyrus (visual area V2) and lingual gyrus, which mediate basic visual processing. Conclusions: To the best of our knowledge, the current meta-analysis is the first to reveal the visualisation, mental rehearsal and motor-related processes underpinning the MVI and offers theoretical support on using MVI as a clinical intervention for post-stroke patients.